(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2018)
This article presents and discusses the findings of a research on the discourse in chemistry classes that was focused on the questions of the teacher and the students. Based on the concept of framing derived from Basil Bernstein’s theory of pedagogical discourse and Hugh Mehan’s initiation types, the research aimed to study the influence of social contexts on the pedagogical practice of Chemistry teachers and its manifestation on their questions in the classroom. Through the analysis, we compared the position of the teacher during the questioning episodes and the types of initiation presented in the questions asked by the teacher and his students. The research methodology was based on a case study, and the data were collected in two urban secondary schools located in different socioeconomic contexts. The results showed differences in the teacher’s position in relation to the both students’ answers and in relation to their questions in both schools, and also differences in the teacher’s position regarding the students’ questions between the schools. Based on the results of our analysis, we identified a relationship between the type of initiation and the degrees of framing of the pedagogical practice. We address these findings with the difference in the pace of the pedagogical practices between the schools and the mode of teacher´s control in front of the students of the two schools. These differences generated different chains of interaction and questions with different conceptual levels.